PERILAKU PIDANA AGRESI JAHAT: Analisis Kekejaman dan Kedestruktifan Manusia - Irwan Ledang; Siti Mutiaraningsih Assagab; Eman Wahyudi Kasim (IAIN Ambon, 2021)
Humans are creatures of God who have physical (body) and non-physical (spirit) elements including soul, mind, and lust. In life, humans have different life goals and obsessions to achieve. As humans are created from the ground and the breath of the divine spirit, it allows them to have both good and evil elements in their natures. The human ability to distinguish what is good and what is bad has led him towards good or bad to the same degree. In this paper, the author focused on evil behavior by analyzing the cruelty and destructive side of humans stimulated by external factors that the Qur'an has already explained about acts related to human crime in many verses. Therefore, it is not surprising that there are many crimes or destructive behavior committed by humans such as actual human destruction (bloodshed), vengeful destructiveness (vengeance), harmful characters (sadism and masochism)Keywords: Behavior, Aggression, Cruelty, Destructive, Humans